2020
DOI: 10.1002/eap.2046
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation and thresholds in hydrological flow‐based ecosystem services

Abstract: Loss and fragmentation of natural land cover due to expansion of agricultural areas is a global issue. These changes alter the configuration and composition of the landscape, particularly affecting those ecosystem services (benefits people receive from ecosystems) that depend on interactions between landscape components. Hydrological mitigation describes the bundle of ecosystem services provided by landscape features such as woodland that interrupt the flow of runoff to rivers. These services include sediment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
1
20
0
4
Order By: Relevance
“…In the past two decades, the population growth, the rapid development of technology, and the real estate industry, and the government’s overall planning policies have aggravated land-use changes in Beijing. It has been demonstrated that land-use change has been identified as one of the most important driving factors of ecological change [ 2 , 56 , 57 ], and, ultimately, is the factor that determines the relative supply and strength of ES, and their interdependent processes [ 4 , 12 , 58 ]. In this study, the expansion of human-built landscapes resulted in the reduction of forest land, water bodies, and cultivated land, which, in turn, reduced the provision of multiple ES and changed the relationships between them as projected under three different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, the population growth, the rapid development of technology, and the real estate industry, and the government’s overall planning policies have aggravated land-use changes in Beijing. It has been demonstrated that land-use change has been identified as one of the most important driving factors of ecological change [ 2 , 56 , 57 ], and, ultimately, is the factor that determines the relative supply and strength of ES, and their interdependent processes [ 4 , 12 , 58 ]. In this study, the expansion of human-built landscapes resulted in the reduction of forest land, water bodies, and cultivated land, which, in turn, reduced the provision of multiple ES and changed the relationships between them as projected under three different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Neutral landscape models have been applied for understanding effects of landscape pattern on movements of single and interacting biota (Etherington 2016;With 1997) ). Our systematic generation of combined topography and land cover patterns also adds to simulations of changed patch sizes on actual topographies (Thomas et al 2020). By capturing some of the main constraints to land use distribution and ecosystem service supply they allow a structured approach to understand and predict ES interactions and multifunctionality.…”
Section: Discussionmentioning
confidence: 99%
“…level of fragmentation) on multifunctionality and their interactions with welldocumented effects of composition, that is the representation of different land uses, and especially functionally critical uses like intensive agriculture and native forest. Thomas et al 2020) show that all ecosystem services (ES) respond to some degree to landscape pattern (composition and con guration) given its in uence on ecological and social processes (Duarte et al 2020). How landscape pattern affects ES pairwise interactions and ES multifunctionality is more complex to understand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LUCI has a proven record of providing reliable output for exploring the impact of land use or management changes on ecosystem service provision in multiple countries, enabling better spatial planning of land management interventions (Emmett et al 2017;Thomas et al, 2019;Tomscha et al, 2019;Pedersen Zari et al, 2020). Uniquely, LUCI is able to model at a range of spatial scalesfrom field or plot level up to catchment/watershed or even national level (Sharps et al, 2017;Emmett et al, 2017, Thomas et al, 2019. It is also capable of comparing different ecosystem services at once, identifying where co-benefits or trade-offs may exist in the landscape.…”
Section: Implementation/applicationmentioning
confidence: 99%